Pharmacokinetic Disposition of Amiodarone When Given with an Intralipid Rescue Strategy - Sean N. Avedissian; Michelle Pham; Medha D. Joshi; Marc H. Scheetz; Ashkan Salamatipour; Jeffin M. Panickar; Khrystyna Hlukhenka; Cristina Miglis; Athanasios Chalkias; Theodoros Xanthos (MDPI AG, 2021)
While the antiarrhythmic drug amiodarone is commonly used in clinical practice, it has a narrow therapeutic index that can lead to acute overdose. One proposed method to deal with this toxicity is lipid emulsion therapy, which may potentially quench the free amiodarone in blood and prevent its further distribution to target organs and tissues. In this study, we utilize an established swine model to examine the effects of Intralipid™ (IL) administration for acute amiodarone toxicity. A total of 14 pigs received an overdose of intravenous amiodarone. After twenty minutes, half of the pigs (n = 7) received IL while the control group (n = 7) received normal saline. Serum concentrations of amiodarone were then analyzed using a validated high-performance liquid chromatography (HPLC) method. Noncompartmental pharmacokinetic analyses were performed on the observed concentrations. There were no statistical differences in the area under the concentration time curve (6 h) or clearance, but there was a difference in the half-life between the two groups (3.12 vs. 0.85 h, p = 0.01). The administration of IL did not statistically change the overall exposure of amiodarone in the blood in the first 6 h; however, trends toward prolonged blood retention in the IL group were seen.